New Prophylactic and Therapeutic Strategies for Spinal Cord Injury - Park, Sookyoung (J Lifestyle Med, 2013)
Melatonin production by the pineal gland in the vertebrate brain has attracted much scientific attention. Pineal melatonin is regulated by photoperiodicity, whereas circadian secretion of melatonin produced in the gastrointestinal tract is regulated by food intake. Thus, the circadian rhythm of pineal melatonin depends upon whether a species is diurnal or nocturnal. Spinal cord injury (SCI) involves damage to the spinal cord caused by trauma or disease that results in compromise or loss of body function. Melatonin is the most efficient and commonly used pharmacological antioxidant treatment for SCI. Melatonin is an indolamine secreted by the pineal gland during the dark phase of the circadian cycle. Neurorehabilitation is a complex medical process that focuses on improving function and repairing damaged connections in the brain and nervous system following injury. Physical activity associated with an active lifestyle reduces the risk of obesity, cardiovascular disease, type 2 diabetes, osteoporosis, and depression and protects against neurological conditions, including Parkinson’s disease, Alzheimer’s disease, and ischemic stroke. Physical activity has been shown to increase the gene expression of several brain neurotrophins (brain-derived neurotrophic factor [BDNF], nerve growth factor, and galanin) and the production of mitochondrial uncoupling protein 2, which promotes neuronal survival, differentiation, and growth. In summary, melatonin is a neural protectant, and when combined with therapeutic exercise, the hormone prevents the progression of secondary neuronal degeneration in SCI. The present review briefly describes the pathophysiological mechanisms underlying SCI, focusing on therapeutic targets and combined melatonin and exercise therapy, which can attenuate secondary injury mechanisms with minimal side effects.